2020
DOI: 10.1089/ars.2018.7687
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Improves Heart Regeneration in Zebrafish

Abstract: Aims: Nitrite is reduced to nitric oxide (NO) under physiological and pathological hypoxic conditions to modulate angiogenesis and improve ischemia-reperfusion injury. Although adult mammals lack the ability to regenerate the heart after injury, this is preserved in neonates and efforts to reactivate this process are of great interest. Unlike mammals, the adult zebrafish maintain the innate ability to regenerate their hearts after injury, providing an important model to study cardiac regeneration. We thus expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Increased methemoglobin level can cause congenital enzymatic defects, variation in hemoglobin molecule [41,42]. Methemoglobin does not bind to oxygen e ciently causing a Loading [MathJax]/jax/output/CommonHTML/jax.js reduction in the oxygen carrying capacity of the blood and reduction in saturated oxygen and oxygen content this decrease is signi cant in high doses of nitrates [43]. Vitamin C protects the blood from the oxidant effect of nitric oxide (antioxidant effect) and induces decreasing of level of met-hemoglobin concentration [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased methemoglobin level can cause congenital enzymatic defects, variation in hemoglobin molecule [41,42]. Methemoglobin does not bind to oxygen e ciently causing a Loading [MathJax]/jax/output/CommonHTML/jax.js reduction in the oxygen carrying capacity of the blood and reduction in saturated oxygen and oxygen content this decrease is signi cant in high doses of nitrates [43]. Vitamin C protects the blood from the oxidant effect of nitric oxide (antioxidant effect) and induces decreasing of level of met-hemoglobin concentration [42].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in methemoglobin levels induced by vitamin C concluded that erythrocyte alone had a negligible ability to reduce methemoglobin in the absence of exogenous ascorbate. Ascorbic acid preserves the Hb in a reduced ferrous redox state [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, it also plays other less known physiological roles, including in the cardiovascular system, where it lowers blood pressure, induces negative inotropic and chronotropic effects, and serves as an anti-inflammatory and anti-oxidant (Garrott et al, 2017; Gutkowska et al, 2014; Jankowski et al, 2020). Many of these actions are carried out by OXT-mediated release of atrial natriuretic peptide (ANP) and nitric oxide (NO) (Jankowski et al, 2020), which have well-characterized cardioprotective effects (Jones & Bolli, 2006; Nishikimi et al, 2006) and may themselves contribute to heart regeneration (Kook et al, 2003; Rochon et al, 2020). Notably, OXT also induces differentiation of cardiomyocytes from embryonic stem cells (Paquin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier this year, it was described how nitric oxide—the reduced form of nitrite, which occurs under hypoxic conditions—improved angiogenesis, immune cell recruitment, and cardiomyocyte proliferation following both cryoinjury and ventricular resection. 76 …”
Section: Vascular Regenerationmentioning
confidence: 99%